Transition-to-home arrangements for very preterm infants and related parental needs at perinatal centres in Austria and Switzerland: a cross-sectional multicentred study - Dirk Bassler; Beatrice Latal; Mark Adams; Juliane Schneider; Jean-François Tolsa; Jörg Jahnel; André Kidszun; Philipp Meyer; Riccardo E Pfister; Martin Stocker; Angelika Berger; Berndt Urlesberger; et al. (BMJ Paediatrics Open)
Introduction The current study aims to give an overview of transition-to-home services provided by perinatal centres in Austria and Switzerland and to evaluate parental satisfaction with the care provided.Methods This cross-sectional multicentred study was conducted by performing two surveys between May 2022 and November 2023: one among all level III perinatal centres in Austria (n=7) and Switzerland (n=9) (institutional survey) and one among parents of very preterm infants treated at one selected perinatal centre in each of the two countries (parental survey). Both questionnaires consisted of matching questions focusing on current transition-to-home services.Results All perinatal centres participated in the institutional survey and 61 out of 84 parents completed the parental questionnaire (response rate 72.6%). The discharge process to home was identified as a multidisciplinary effort involving various healthcare professionals with discrepancies in responses within and between institutional and parental questionnaires. Certain disparities were observed in the timing of discharge conversations between healthcare providers and parents. Most physicians mentioned initiating discharge discussions while the child was still in the intensive care unit, but only 14.8% of parents recalled these early conversations. One-fourth of perinatal centres actively contact patients after discharge. So far, video consultations or mobile applications have not been offered. While 95.1% of parents expressed satisfaction with the care received, there were concerns about contradictory medical information, particularly regarding breastfeeding.Conclusion The transition-to-home process for very preterm infants presents several opportunities for improvement, especially concerning communication between healthcare providers and parents, lactation counselling services and the timely outreach to parents shortly after discharge. The findings of the current study may further improve this transition process and might aid in the development of a standardised programme that is tailored to parental needs.